Rapports de Parcs Canada
Portail de publications électroniques sur l’histoire culturelle et naturelle du réseau des parcs nationaux du Canada, qui inclut comprend 48 parcs nationaux / réserves, un parc urbain national, 1,007 lieux historiques nationaux (dont 171 sont administrés par Parcs Canada, y compris neuf canaux du patrimoine), quatre aires marines de conservation nationales, un point de repère national, ainsi que des documents de l'histoire de l'agence chargée de gérer ce système: Parcs Canada.
Keywords: _open access

Admission des enfants assistés (Archives de Paris)
Keywords: _open access

Fondamentaux des sciences et des techniques Sciences
Keywords: _open access

Galligeo. géoréférencer les cartes anciennes du site Gallica (BnF)
Le consortium Huma-Num Projets Time Machine (PTM) propose Galligeo, une application web qui permet de géoréférencer les cartes anciennes du site Gallica (BnF). Fruit d’un partenariat entre le BNF Datalab, Gallica, Huma-Num (CNRS) et le consortium PTM, Galligeo, c’est : la possibilité de contribuer sans compte ou, pour les chercheurs, via une connexion ORCID, un outil ouvert à toutes et tous : chercheurs, enseignants, étudiants mais aussi grand public, la constitution d’un fonds collaboratif de cartes et plans géoréférencés, librement consultables et réutilisables, un dépôt simplifié sur Nakala pour assurer la pérennité et la citabilité des données, la possibilité de créer et partager des atlas à partir des cartes géoréférencées. https://cartonumerique.blogspot.com/2025/10/galligeo-un-outil-en-ligne-pour.html
Keywords: _open access

Projets Time Machine. Construire et diffuser ensemble des référentiels géohistoriques (Projets Time Machine)
Keywords: _open access

Royal Ontario Museum
Collections consacrées à l’art, à la nature et aux cultures du monde entier et de toutes les époques
Keywords: _open access

Digital Bodleian
Keywords: _open access

Corpus Académie française (ORTOLANG)
Le Corpus Académie française est un corpus lemmatisé et étiqueté des textes publiés sur le site de l'Académie française dans les rubriques « Discours », « Dire, ne pas dire » et « Questions de langue. 1635 à nos jours.
Keywords: _open access

Mamluk Bibliography Online (2006)
Keywords: _open access

Digital Matteo Ricci
Le projet Matteo Ricci est centré sur la publication numérique de la correspondance du missionnaire jésuite pour la première fois en français. S’il existe deux éditions en langues originales de ses lettres, celle de Pietro Tacchi Venturi de 1913 et celle de Filippo Mignini en 2001, jamais encore elles n’avaient fait l’objet d’une traduction in extenso et d’un appareil critique approfondi. L’inventaire, enrichi de nouvelles pièces, donne accès au descriptif de chaque document, à son édition critique et à sa traduction. Le projet nourrit l’ambition de reconstituer la correspondance passive et périphérique, si possible à partir des sources de première main (autographes et apographes contemporains de Ricci). L’idée est de mettre ce travail inédit en perspective avec les autres productions de Ricci notamment son journal de mission, ses œuvres chinoises et une riche iconographie. La thésaurisation de tous les documents réunis ici (notices biographiques, images, notices thématiques...) permet un accès à la vaste production de Matteo Ricci et à saisir un peu mieux la complexité de cette figure unique de l’histoire des relations entre l’Occident et la Chine.
Keywords: _open access

Ming Qing Women's Poetry Collection (CALASYS - CALA Academic Resources & Repository System)
Keywords: _open access

Ming Qing women's writings
This digital archive is a collaborative project among the libraries, including the McGill Library, the Harvard-Yenching Library, and the Peking University Library. As of December 2022, the archive provides free online access to 426 collections of women's writings published during Ming (1368-1644), Qing (1644-1911), and the Republican (1911-1949) periods. Users can search and browse more than 70,000 scanned images of texts and illustrations by the 5,240 women poets and writers and the 2,475 male writers who contributed to women's writings as editors/compilers or as writers of prefaces, biographies, endorsement verse, and postscripts.
Keywords: _open access

Biblioteca Digital del Museo del Prado
5600 números de revistas y 6000 libros publicados entre finales del siglo XV y principios del siglo XX
Keywords: _open access

Recherche d'une mention dans le répertoire des actes d'état civil (baptêmes, mariages, sépultures) 1621-1861 (PRDH-IGD, Programme de recherche en démographie historique - Institut généalogique Drouin)
Keywords: _open access

Chinese collections at the Bodleian Libraries - Bodleian Libraries (2024)
Chinese books have been part of the Bodleian Libraries’ collections since the Library’s foundation in 1602. The first known acquisition of a Chinese book dates to 1604. Our founder – Sir Thomas Bodley – was instrumental in starting this collection, even though he did not speak or understand Chinese.  His handwriting appears in the 1604 book. The collection grew over the following four centuries and it continues to grow today. It is now one of the most significant Chinese rare book and manuscript collections outside China, containing the largest number of Chinese books that arrived in Europe in 17th century. As part of a ten-year project funded by Chung Hon Dak Foundation, we have digitised over 1,800 items, as well as worked with the local Chinese community to explore our collections in more detail.
Keywords: _open access

French Revolution Publications Collection (University of Kentucky Libraries, 2024)
5000 political bulletins, printed from the beginning of the long and bloody French Revolution through the ascendancy of Napoleon Bonaparte
Keywords: _open access

Dataset Card for British Library Books
We’re on a journey to advance and democratize artificial intelligence through open source and open science.
Keywords: _open access

French-Public Domain-Book
We’re on a journey to advance and democratize artificial intelligence through open source and open science.
Keywords: _open access

BnF Archives et manuscrits
Keywords: _open access

The Book of Negroes Data - Dragovich, Joe (2022)
A JSON formatted version of the 1783 historical document The Book of Negroes. In 1783, the new United States demanded that the British return the enslaved people that had fled to their lines during the war. The British refused and evacuated them from New York.
Keywords: _18e; _open access

Remonter le temps - IGN
Consultation et impression de données anciennes et actuelles
Keywords: _open access

Recently Digitized Manuscripts from the BAV (Biblioteca Apostolica Vaticana) (Vatican Manuscript Tracking)
This is a project to track the work of the Biblioteca Apostolica Vaticana in digitizing their collection of over 80,000 manuscripts.
Keywords: _open access

Old Bailey Online - The Proceedings of the Old Bailey, 1674-1913 - Central Criminal Court
Keywords: _open access

Slave Voyages
Keywords: _open access

AARDOC: African-American Religion: A Documentary History Project Home Page
Keywords: _open access

British History Online
The core printed primary and secondary sources for the medieval and modern history of the British Isles
Keywords: _open access

Early Americas Digital Archive
A collection of electronic texts originally written in or about the Americas from 1492 to approximately 1820.
Keywords: _open access

Canadian Pamphlets and Broadsides - Thomas Fisher Rare Book Library
This collection provides access to the pre-1930 Canadian pamphlet and broadside holdings of the Thomas Fisher Rare Book Library by supplying both page images in full colour, and full searchability of the contents of each item. To date the site consists of 597 broadsides (single sheets, printed on one or both sides) and 2,062 pamphlet titles which amounts to 71,508 page images. The collection includes items printed in Canada, by Canadian authors, or about Canadian subjects, mainly of a non-literary nature.
Keywords: _open access

French Revolution Digital Archive
Keywords: _open access

The Fur Trade in Canada - La traite des fourrures au Canada
Site de recherche universitaire illustrant l'âge épique de la traite des fourrures au Canada en retraçant les hauts faits de la Compagnie du Nord-Ouest et d'autres entreprises de traite de Montréal à la fin du XVIIIe et au début du XIXe siècle
Keywords: _open access

Dossier France-Amérique - BNF; Library of Congress
Le site explore l'histoire de la présence française en Amérique du Nord depuis les premières décennies du XVIe siècle jusqu'à la fin du XIXe siècle
Keywords: _open access

Vatican Apostolic Library
Keywords: _open access

Archives apostoliques du Vatican
Keywords: _open access

Répertoire du patrimoine culturel du Québec
Keywords: _open access

Musée de la civilisation (Collections - Musée de la civilisation)
Plus d’un quart de million d’objets. More than a quarter of a million objects.
Keywords: _open access

Musée virtuel de la Nouvelle-France (Musée canadien de l’histoire)
Keywords: _open access

Musée canadien de l'histoire
Ancien Musée canadien des civilisations, et avant cela Musée national de l’Homme
Keywords: _open access

Les archives du Monastère des Augustines
Les archives des Augustines permettent de retracer l’évolution des soins de santé, du développement social, de la vie en communauté et de l’établissement de douze hôpitaux au Québec depuis les premiers temps de la colonie.
Keywords: _open access

BAnQ numérique
Partez à la découverte de BAnQ numérique. 1524 - 1970s. French and English language periodicals from Quebec.
Keywords: _open access

Artefacts Canada - Gouvernement du Canada, Ministère du Patrimoine canadien
Artefacts Canada propose un accès à de l'information sur des millions d'objets de musées, fournis par des musées et des organismes patrimoniaux de partout au Canada.
Keywords: _open access

Archives de la Nouvelle-France
Keywords: _open access

Advitam (Advitam)
La nouvelle interface des Archives nationales
Keywords: _open access

Les Relations des jésuites, 1570-1720
Keywords: _open access

Quebec Herald (1788-1791)
Keywords: _open access

Recensements du Canada 1665 à 1871 : Nouvelle-France, Bas-Canada, Québec
Keywords: _open access

Persian Language Rare Materials (Library of Congress)
The Library of Congress is home to a noteworthy collection of rare Persian language manuscripts, lithographic books and early imprints, as well as printed books, housed in the African and Middle Eastern Division (AMED) and the Rare Book and Special Collections Division. Most of these Persian manuscripts and lithographic books were procured for the Library  in the 1930s by Kirkor Minassian (1874-1944), a renowned dealer in fine Islamic and Near Eastern arts with establishments both in New York and Paris. The Minassian  acquisitions included treasures from the entire Middle East with rare books and manuscripts in Arabic, Persian, Turkish and Armenian languages.  Since the 1930s  the Library has continued to purchase a small number of Persian language manuscripts and lithographs at auctions, and from antique manuscript  and book sellers  including  Christies and Sotheby's. The Library has also benefited from the generosity of people who have donated rare Persian materials they inherited from their families over the generations and which have been present in the United States or Europe  before World War II.
Keywords: _open access

The National Archives, UK
Official archive of the UK government, and for England and Wales.. Spanning 1000 years of history. Non-ministerial department.
Keywords: _open access

World Historical Gazetteer
Index of place records with coordinates, historical metadata, linked toponyms, and ecological classifications
Keywords: _open access

Monasterium
Keywords: _open access

Project Gutenberg (Project Gutenberg)
Project Gutenberg is a library of free eBooks.
Keywords: _open access

Gallica
Keywords: _open access